Synthesis and research on properties of 2-(4-еthyl-5-((3’-methylxantine-7’-yl)methyl)-4H-1,2,4-triazole-3-ylthio)acetic acid’s salts - Gotsulya, A. S.; Гоцуля, Андрій Сергійович; Гоцуля, А. С. (Запорізький державний медичний університет, 2016)
1,2,4-Triazole derivatives are successfully used in medicine as antibacterial and antifungal agents. Aim of our research is the study of synthesis of 7’-((3-thio-4-ethyl-4H-1,2,4-triazole-5-yl)methyl)-3’-methylxanthine. Methods and results. Sodium salt of 3-methylxanthine has been used as the initial substance to obtain a new series of these compounds. It has been shown that the reaction of the corresponding hydrazide interaction with ethylisothiocyanate fi nds its continuation in the intramolecular cyclization. The synthesis of 2-(4-ethyl-5-((3’-methylxantine-7’-yl) methyl)-4Н-1,2,4-triazol-3-ylthio)аcetic acid’s salts has been performed. Physical-chemical properties of compounds have been researched and their structure and individuality has been confi rmed by elemental analysis, IR-spectroscopy, 1H NMR-spectroscopy, chromatomass and mass-spectrometry. Conclusion. 12 New compounds have been obtained and their structure has been confi rmed. Похідні 1,2,4-тріазолу успішно використовуються в медичній практиці як протимікробні та протигрибкові засоби. Метою нашого дослідження був синтез 7’-((3-тіо-4-етил-4Н-1,2,4-тріазол-5-іл)метил)-3’-метилксантину. Як вихідну сполуку для отримання цільового ряду сполук використали натрієву сіль 3-метилксантину. Показано, що реакція взаємодії відповідного гідразиду з етилізотіоціанатом знаходить своє продовження у внутрішньомолекулярній циклізації. Здійснили синтез солей 2-(4-етил-5-((3’-метилксантин-7’-іл)метил)-4Н-1,2,4-тріазол-3-ілтіо)ацетатної кислоти. Досліджені фізико-хімічні властивості сполук, що одержали, та підтверджена їхня будова за допомогою елементного аналізу, 1Н ЯМР-спектрометрії, ІЧ-спектрофотометрії, хромато-мас- і мас-спектрометрії. Отримали 12 сполук, підтверджена їхня структура. Производные 1,2,4-триазола успешно используются в медицинской практике в качестве антимикробных и противогрибковых средств. Осуществлён синтез 7’-((3-тио-4-этил-4Н-1,2,4-триазол-5-ил)метил)-3’-метилксантина. В качестве исходного вещества для получения целевого ряда соединений была использована натриевая соль 3-метилксантина. Показано, что реакция взаимодействия соответствующего гидразида с этилизотиоцианатом находит своё продолжение во внутримолекулярной циклизации. Проведён синтез солей 2-(4-этил-5-((3’-метилксантин-7’-ил)-метил)-4Н-1,2,4-триазол-3-илтио)ацетатной кислоты. Исследованы физико-химические свойства полученных соединений и подтверждено их строение с помощью элементного анализа, 1Н ЯМР-спектрометрии, ИК-спектрофотометрии, хромато-масс- и масс-спектрометрии. Получены 12 соединений и подтверждена их структура.
Синтез і дослідження властивостей солей 2-(4-етил-5-((3’-метилксантин-7’-іл)метил)-4Н-1,2,4-тріазол-3-ілтіо)ацетатної кислоти
Синтез и исследование свойств солей 2-(4-этил-5-((3’-метил-ксантин-7’-ил)метил)-4Н-1,2,4-триазол-3-илтио) ацетатной кислоты
Keywords: Xanthines; 1,2,4-triazole; Physical and Chemical Properties; 3-метилксантин; 1,2,4-тріазол; фізико-хімічні властивості; 3-метилксантин; 1,2,4-триазол; физико-химические свойства